2023
DOI: 10.3390/fishes8050255
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Polyphenol-Based Synbiotics in Crustacean Diet

Abstract: Here, the olive leaf extract (OLE) rich in polyphenols was employed as a prebiotic agent, together with Lactobacillus reuteri and Bacillus clausii, to develop synbiotics. The prebiotic effect of olive leaf extract on the probiotic strains was tested at concentrations of 0, 50, 100, 400, and 1000 μg mL−1, and also 20 and 40 mg mL−1. Olive leaf extract at 40 mg mL−1 showed the best prebiotic activity on L. reuteri and B. clausii. A basal diet and two experimental synbiotic-containing diets were prepared. The syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 110 publications
0
1
0
Order By: Relevance
“…Growing scientific evidence suggests that polyphenolic molecules have the potential to exert important bioactive properties [ 9 , 10 ], including antimicrobial effects [ 11 ]. Several recent studies have shown how polyphenols extracted from different botanical matrices are able to exert significant in vitro antibacterial and antifungal activity in in vitro models and beneficial effects in in vivo systems [ 12 , 13 , 14 , 15 , 16 , 17 ]. Regarding waste from vine-winery chains, some studies have demonstrated the antibacterial potential of polyphenolic extracts from winemaking byproducts [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Growing scientific evidence suggests that polyphenolic molecules have the potential to exert important bioactive properties [ 9 , 10 ], including antimicrobial effects [ 11 ]. Several recent studies have shown how polyphenols extracted from different botanical matrices are able to exert significant in vitro antibacterial and antifungal activity in in vitro models and beneficial effects in in vivo systems [ 12 , 13 , 14 , 15 , 16 , 17 ]. Regarding waste from vine-winery chains, some studies have demonstrated the antibacterial potential of polyphenolic extracts from winemaking byproducts [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%